Manajemen BKM At-Tawwabin Jalan Pimpinan Kota Medan dalam Pemberdayaan Ekonomi Masyarakat - Wahyu Andreansyah Siregar; Soiman Soiman (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to know the management of the Mosque Prosperity Board (BKM) of At- Tawwabin Mosque, Jalan Pimpinan, Medan City, in community economic empowerment. The background of this research is based on the need to optimize the function of mosques not only as places of ritual worship but also as centers of social and economic empowerment. In practice, the management of mosque assets such as parking areas and the organization of Ramadan stalls has become a strategic effort implemented by BKM to improve the welfare of the surrounding community. However, the implementation of these policies also creates social dynamics that require professional and equitable management.This research employs a qualitative approach with a descriptive method. Data were collected through field observations, in-depth interviews with the chairman and administrators of BKM, parking attendants, and Ramadan stall traders, as well as documentation of mosque activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, supported by triangulation techniques to ensure data validity.The findings indicate that the management of BKM At-Tawwabin has implemented planning, organizing, actuating, and controlling functions in managing mosque-based economic programs. Parking management provides employment opportunities for local residents, while Ramadan stalls significantly increase the income of small traders during the holy month. Overall, participatory and structured management enables the mosque to function not only as a center of worship but also as a center of economic empowerment that contributes meaningfully to community welfare.